Effect of partial oxidation by ozonation on the photocatalytic degradation of humic acids - (:unkn) unknown (My University, 2003)
In this study humic acids, which are known to be a heterogeneous group of organic macromolecules found in natural waters, were oxidized using ozonation and photocatalysis in a sequential system. Ozonation was employed for achieving partial oxidation of humic acids prior to photocatalytic oxidation. Degradation of humic acid was explained by using pseudo first order reaction rate model based on UV-vis measurements. An improvement was achieved in the photocatalytic degradation rates with respect to the degree of pre-oxidation by ozonation. Due to the surface oriented nature of photocatalysis, adsorption characteristics of partially oxidized humic acid samples on TiO 2 photocatalyst were evaluated by the application of the Freundlich adsorption model. The photocatalytic degradation rates did not correlate well with the dark adsorption characteristics of the pre-ozonated as well as untreated humic acid samples.